Childhood Maltreatment and Trauma: Critical Appraisal - Niken Setyaningrum (GLOBAL HEALTH SCIENCE GROUP, 2025)
Childhood abuse and trauma can cumulatively become interpersonal stress in adulthood. Trauma that often occurs includes emotional abuse, physical violence, and other trauma. The purpose of this paper is to conduct a critical assessment to determine the research method used in a study so that the results obtained are reliable. The research article conducted by Malcom in 2017 entitled Childhood maltreatment and trauma are common and serious in body dysmorphic disorder. This critical appraisal needs to be done to assess the research conducted using the correct method and the results are reliable. The method used is the Checklist for Analytical Cross-Sectional Studies from JBI (Joanna Briggs Institute) which consists of 8 question items, namely (1) inclusion criteria in the sample (2) Population description and demographic data (3) Risk factors and interventions (4) Valid measuring instruments (5) Confounding factors (6) Factors that influence variables (7) Measurement results (8) Statistical analysis. The results of the critical appraisal conducted in the article mention that it has many advantages such as the use of validated measuring instruments and appropriate statistical analysis, but there are inputs that can be used as considerations for further research, namely the control of confounding factors and limitations in the cross-sectional study design which only shows associative relationships.